Periodontal ligament influence on the stress distribution in a removable partial denture supported by implant: a finite element analysis - Archangelo, Carlos Marcelo; Rocha, Eduardo Passos [UNESP]; Pereira, Joao Antonio [UNESP]; Martin Junior, Manoel; Anchieta, Rodolfo Bruniera [UNESP]; Freitas Junior, Amilcar Chagas [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2012)
Objective: The non-homogenous aspect of periodontal ligament (PDL) has been examined using finite element analysis (FEA) to better simulate PDL behavior. The aim of this study was to assess, by 2-D FEA, the influence of non-homogenous PDL on the stress distribution when the free-end saddle removable partial denture (RPD) is partially supported by an osseointegrated implant. Material and Methods: Six finite element (FE) models of a partially edentulous mandible were created to represent two types of PDL (non-homogenous and homogenous) and two types of RPD (conventional RPD, supported by tooth and fibromucosa; and modified RPD, supported by tooth and implant [10.00x3.75 mm]). Two additional FE models without RPD were used as control models. The non-homogenous PDL was modeled using beam elements to simulate the crest, horizontal, oblique and apical fibers. The load (50 N) was applied in each cusp simultaneously. Regarding boundary conditions the border of alveolar ridge was fixed along the x axis. The FE software (Ansys 10.0) was used to compute the stress fields, and the von Mises stress criterion (sigma vM) was applied to analyze the results. Results: The peak of sigma vM in non-homogenous PDL was higher than that for the homogenous condition. The benefits of implants were enhanced for the non-homogenous PDL condition, with drastic sigma vM reduction on the posterior half of the alveolar ridge. The implant did not reduce the stress on the support tooth for both PDL conditions. Conclusion: The PDL modeled in the non-homogeneous form increased the benefits of the osseointegrated implant in comparison with the homogeneous condition. Using the non-homogenous PDL, the presence of osseointegrated implant did not reduce the stress on the supporting tooth.
Keywords: Removable partial denture; Dental implant; Finite element analysis; Periodontal ligament